2004
DOI: 10.1096/fj.04-2031fje
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3/AGE‐receptor 3 knockout mice show accelerated AGE‐induced glomerular injury: evidence for a protective role of galectin‐3 as an AGE receptor

Abstract: We previously showed that mice lacking galectin-3/AGE-receptor 3 develop accelerated diabetic glomerulopathy. To further investigate the role of galectin-3/AGE-receptor function in the pathogenesis of diabetic renal disease, galectin-3 knockout (KO) and coeval wild-type (WT) mice were injected for 3 months with 30 microg/day of N(epsilon)-carboxymethyllysine (CML)-modified or unmodified mouse serum albumin (MSA). Despite receiving equal doses of CML, KO had higher circulating and renal AGE levels and showed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 72 publications
10
114
4
1
Order By: Relevance
“…Moreover, an increased amount of AGE-R1 suppresses AGE-mediated mesangial cell inflammatory injury through negative regulation of RAGE signalling [10]. AGE-R3, which is encoded by LGALS3, also seems to participate in the degradation of AGEs, since knockout mice for AGE-R3 have higher AGE levels in the kidneys and a higher incidence of age-related glomerular lesions [11]. The clustering of genetic risk factors for many autoimmune diseases suggests that these diseases share similar underlying causal mechanisms [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increased amount of AGE-R1 suppresses AGE-mediated mesangial cell inflammatory injury through negative regulation of RAGE signalling [10]. AGE-R3, which is encoded by LGALS3, also seems to participate in the degradation of AGEs, since knockout mice for AGE-R3 have higher AGE levels in the kidneys and a higher incidence of age-related glomerular lesions [11]. The clustering of genetic risk factors for many autoimmune diseases suggests that these diseases share similar underlying causal mechanisms [12].…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular cell apoptosis Glomerular cell death rate was assessed by immunohistochemistry, as previously reported [11,31]. Sections were sequentially treated with: (1) Triton X-100 (0.1%, vol./vol.)…”
Section: Methodsmentioning
confidence: 99%
“…Serum AGE levels were assessed by competitive ELISA, using a mouse monoclonal antibody against AGE-modified bovine serum albumin [11,31].…”
Section: Methodsmentioning
confidence: 99%
“…Metaflammation precedes the development of metabolic abnormalities such as insulin resistance, type 2 diabetes and nonalcoholic fatty liver disease. Despite the fact that Galectin-3 exhibits deleterious effects under inflammatory conditions, various studies have demonstrated its protective role in the pathogenesis of obesity-induced inflammation triggered by accumulation of different metabolic stressors, such as advanced glycation end products (AGEs) (28). Namely, AGEs and the receptor for AGEs (RAGE) have been linked to enhanced apoptosis and dysfunction of pancreatic β cells and also to the pathogenesis of diabetic complications (29).…”
Section: Galectin3 In Inflammation and Autoimmunitymentioning
confidence: 99%